P53 Independent epigenetic-differentiation treatment in xenotransplant models of acute myeloid leukemia - Ng, K. P. (2011)
Suppression of apoptosis by TP53 mutation contributes to resistance of acute myeloid leukemia (AML) to conventional cytotoxic treatment. Using differentiation to induce irreversible cell cycle exit in AML cells could be a p53-independent treatment alternative, however, this possibility requires evaluation. In vitro and in vivo regimens of the deoxycytidine analogue decitabine that deplete the chromatin-modifying enzyme DNA methyl-transferase 1 without phosphorylating p53 or inducing early apoptosis were determined. These decitabine regimens but not equimolar DNA-damaging cytarabine upregulated the key late differentiation factors CCAAT enhancer-binding protein and p27/cyclin dependent kinase inhibitor 1B (CDKN1B), induced cellular differentiation and terminated AML cell cycle, even in cytarabine-resistant p53-and p16/CDKN2A-null AML cells. Leukemia initiation by xenotransplanted AML cells was abrogated but normal hematopoietic stem cell engraftment was preserved. In vivo, the low toxicity allowed frequent drug administration to increase exposure, an important consideration for S phase specific decitabine therapy. In xenotransplant models of p53-null and relapsed/refractory AML, the non-cytotoxic regimen significantly extended survival compared with conventional cytotoxic cytarabine. Modifying in vivo dose and schedule to emphasize this pathway of decitabine action can bypass a mechanism of resistance to standard therapy. © 2011 Macmillan Publishers Limited All rights reserved.